2016
DOI: 10.7150/thno.16514
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Fluorescent Nanoparticles Derived from Hyaluronic Acid Improve Tumor Contrast for Image-Guided Surgery

Abstract: Tumor tissue that remains undetected at the primary surgical site can cause tumor recurrence, repeat surgery, and treatment strategy alterations that impose a significant patient and healthcare burden. Intraoperative near infrared fluorescence (NIRF) imaging is one potential method to identify remaining tumor by visualization of NIR fluorophores that are preferentially localized to the tumor. This requires development of fluorophores that consistently identify tumor tissue in different patients and tumor types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 41 publications
7
45
0
Order By: Relevance
“…Prior to TEM imaging, NPs (concentration 1.0 mg/mL in PBS) were placed on a formvar/silicone monoxide-coated 200 mesh copper grid and allowed to adhere for approximately 5 min, NanoVan negative stain was applied for 30 s, and the sample was blotted to remove excess solvent or material. TEM images of NanoICG and NanoCy7.5 10k-PBA NPs are also provided in our previous publications [23,32,33]. The stability of NanoICG PBA in a solution of PBS containing bovine serum albumin (BSA) has been reported [23], showing that ICG was rapidly released into albumin-containing solution across a dialysis membrane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to TEM imaging, NPs (concentration 1.0 mg/mL in PBS) were placed on a formvar/silicone monoxide-coated 200 mesh copper grid and allowed to adhere for approximately 5 min, NanoVan negative stain was applied for 30 s, and the sample was blotted to remove excess solvent or material. TEM images of NanoICG and NanoCy7.5 10k-PBA NPs are also provided in our previous publications [23,32,33]. The stability of NanoICG PBA in a solution of PBS containing bovine serum albumin (BSA) has been reported [23], showing that ICG was rapidly released into albumin-containing solution across a dialysis membrane.…”
Section: Methodsmentioning
confidence: 99%
“…TEM images of NanoICG and NanoCy7.5 10k-PBA NPs are also provided in our previous publications [23,32,33]. The stability of NanoICG PBA in a solution of PBS containing bovine serum albumin (BSA) has been reported [23], showing that ICG was rapidly released into albumin-containing solution across a dialysis membrane. It was also shown that a NanoCy7.5 variant with aminopropyl-5β-cholanamide as the conjugated hydrophobic moiety, NanoCy7.5 100k-5βCA , showed limited disassembly into albumin-containing solution over a 6 h period, and then gradual disassembly over the next 72 h [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…liver and speen. 4951 Liver cells express stabilin-2 (sub-family of CD44) and spleen cells have high expression of CD44. 52 Similar results were observed by Lin et al 53 , where HA-IR-780-based nanosystems accumulated largely in liver and spleen.…”
Section: Introductionmentioning
confidence: 99%
“…Impressively, their migration in vivo not only can be monitored by MRI, but also by intravital TPL at the microscopic level, allowing for precise photothermal- and chemo- combination therapy. Mohs et al synthesized a panel of hyaluronic acid (HA) based nanoparticles that were either physically entrapped with indocyanine green (ICG) or covalently conjugated with Cy7.5 3. These formulations were evaluated as intraoperative optical imaging agents for accurate tumor removal.…”
mentioning
confidence: 99%